Діалектні елементи у мовному ландшафті Закарпаття: перелік слів та історичний підхід до їх вивчення - Шилов, Володимир (SlavVaria, 2026)
Dialectal Elements in the Linguistic Landscape of Transcarpathia: A Word List and a Historical Approach to Their Study. The article analyzes the use of dialectal elements of the Ukrainian language in street inscriptions in the Transcarpathian region. The data were collected in the summer of 2021 in various cities of Transcarpathia, including Uzhhorod, Mukachevo, Khust, Berehove, Rakhiv, Tiachiv, Chop, and Irshava. A diachronic analysis was then carried out, involving the search for these words in dictionaries of Transcarpathian vocabulary from different historical periods. The result of this analysis is a table indicating when each dialectal element was first documented. Thus, it becomes possible to expand the scope of linguistic landscape research by linking it to dialectology.